Neutrophilic figurate erythema of infancy: A diagnostic challenge. (26th December 2018) - Hamidi, Sepehr; Prose, Neil S.; Selim, Maria A.
Abstract : Neutrophilic figurate erythema of infancy (NFEI) is a rare variant of annular erythema of infancy. It is characterized by annular erythematous plaques, occasionally with a polycyclic configuration. The main challenge is to differentiate this rare entity from other figurate erythemas associated with serious diseases such as neonatal lupus erythematosus. We present the case of a 9‐month‐old female admitted with a skin rash of unclear etiology. The rash started on her face at the age of 3 months and gradually spread to her extremities. She had no constitutional symptoms, and her health and development were otherwise unremarkable since birth. This persistent skin eruption consisted of many ill‐defined erythematous papules and annular plaques. Histologic examination revealed perivascular neutrophils and eosinophils with abundant nuclear dust without signs of vasculitis. NFEI is a diagnostic enigma both clinically and histologically. Absence of an underlying cause, dermal neutrophilic infiltrate with leukocytoclasis, and lack of vascular damage are the keys to diagnosis.